From imaginative experiments to inventive performances: On the role of creativity in the developmental experiences of professional ice hockey players - Rasmussen, L. J. T.; Dalsgaard, S. H. (The Sport Psychologist, 2023)
Despite an increasing interest in studying creativity in sport, previous research has primarily focused on in-game creative performance and employed research designs neglecting sport participants` perspectives. Hence, this study explored professional athletes` developmental experiences involving creativity. Semistructured retrospective interviews were conducted with eight ice hockey players performing in or retired from the National Hockey League, Kontinental Hockey League, or Swedish Hockey League. Players described 15 modalities of creative actions emerging when playing, practicing, and performing. Based on the players` experiences, creativity led to augmented levels of enjoyment (i.e., elicited passion), development (i.e., enhanced potential), achievement (i.e., enriched in-game qualification), and fulfillment (i.e., extended career progression). Findings contribute to a more nuanced understanding of creativity in sport and provide novel insights on the role of creativity in the development and maintenance of expertise in sport and the nature and role of deliberate play and deliberate practice in developing creativity.